Informal Networks: Dark Sides, Bright Sides, and Unexplored Dimensions. (July 2020) - Horak, Sven; Afiouni, Fida; Bian, Yanjie; Ledeneva, Alena; Muratbekova-Touron, Maral; Fey, Carl F.
Abstract: Informal networking can be seen as a positive activity with beneficial outcomes for individuals, firms, and society as a whole, but informal networking can also lead to collusion, cliques, nepotism, and other forms of unethical or corrupt conduct – largely related to research on emerging markets. To date, the construction of informal networks and their cultural intertwinement and development have not been a focus of international management and organization studies, a gap that this special issue seeks to address. This special issue contributes to a better understanding of the dynamics of informal networks and their ambivalence, in which the same networks have different modes of operation and have positive and negative sides intermittently or simultaneously. We demonstrate the context in which informal networks operate, highlight their complexity, and encourage dialogue among scholars studying informal networks in a variety of countries. Using a context-based and comparative perspective allows us to conceptualize informal networks in a more integrated and balanced way. Understanding the workings of informal networking – known variously as guanxi, yongo, jentinho, wasta, and blat – in culturally specific settings, places Western values, social structures, and ideals of behavior in perspective and tests Western-centered assumptions, narratives, and theories. Because informal networking is a conventional way of conducting business in many countries, as depicted in this special issue, defining the bright (positive) and the dark (negative) sides of informal networks is critical for responsible management and business success at multinational corporations.